COLLECTIVE ETHOS IN THE LEGAL PROFESSION - Byrd, Michael Gordon (East Carolina University)
The intersection of rhetoric and professional communication scholarship focuses on persuasion in the workplace. Specifically looking at the legal profession, lawyers occupy a prestigious situation in the United States. Lawyers have the privilege to practice law, such as representing clients, advocating in court, and preserving the quality of justice. Society has placed a special trust in lawyers. This dissertation critically analyses the legal profession’s available means of persuasion to gain and sustain society’s trust. An understudied concept of collective ethos is used to consider how lawyers persuade at the societal level. The core of this dissertation is Burke’s concept of identification. Through an analysis of the Rules of Professional Conduct, genres in the legal professional’s activity system, and Disciplinary Statements of errant lawyers, this dissertation develops and defines the concept of collective ethos for the legal profession and other similarly situated professions. In discussion of these findings, new areas of research are proposed and questions raised for emergent professions seeking to develop and maintain collective ethos.
Keywords: Ethics